Analysis and Experimental Study of Contact Stress in Bolted Connections of Pitch Bearings - Jiuju Zhang; Wanxin Luo; Tao Chen; Xichao Yan; Jiaqi Zhang; Meng Zhu; Hongwei Zhang (Lubricants)
In wind turbine systems, bolted connections in pitch bearings are subjected to working loads that reduce bolt preload. This reduction can lead to issues such as bolt loosening and eccentric loading, which in turn results in the nonuniform distribution of contact stress across joint surfaces. These issues can compromise structural integrity and reduce fatigue life. However, the study of contact stress mainly focuses on theoretical research, lacking relatively large, complex structures. Also, the stress testing methods for contact surfaces of bolted connections are limited in practical engineering. In this paper, a localized bolt connection model using the finite element method according to pitch bearings in wind turbine systems was established. The contact stress distribution patterns of bolt specimens under varying preloads were investigated. Comparative numerical simulation and experimental analysis using thin-film pressure sensors were conducted. Furthermore, the effect of bolt assembly in different tightening processes on the contours of contact stress was analyzed to identify the optimal tightening sequence. The experimental results demonstrate a positive correlation between preload and maximum contact stress, with stress distribution exhibiting symmetry around the bolt hole and decreasing radially outward. Thin-film pressure sensors can be used for contact stress detection. Furthermore, the diagonal tightening method can achieve a more uniform contact stress distribution compared to other methods, such as sequential and alternate tightening. The findings provide valuable insights for optimizing the contact stress distribution and tightening processes in bolted joint assemblies.